Forensic Science and the Forensic Biochemist - Korkor, A.G. (Office of Research, Innovation and Development, University of Ghana, Legon, Accra Ghana., 2023)
Forensic science has received more attention lately and this has led burgeoning of University courses being embedded with it. This book has new case studies with probable exams - oriented questions as well as uncovering the various activities of the forensic biochemist and the need for standardization of protocols. Target group for this book include undergraduates, postgraduates, researchers, and forensic practitioners.
Book
Keywords: Forensic Science; Forensic Biochemist